SPT and CPT Correlation of Expansive Clay in Cikarang, Indonesia - Sudjatmiko, Eddy Triyanto (Journal of the Civil Engineering Forum, 2022)
Several CPT-SPT correlations have been reported worldwide to allow for the estimate of soil physical properties from one set of accessible data to another. Although most correlations are for silty and sandy soils, there is insufficient information on whether these correlations correspond to the silty clay soil conditions in Indonesia. Therefore, this study aims is to validate and enhance the generalized CPT-SPT correlation, with emphasis on Indonesian soil conditions to increase its prediction accuracy. The soil under examination is silty clay layers that cover most of Northern parts of West Java – Indonesia. Known with its expansive clay characteristics, these type of soils are sensitive to volume change as a result of seasonal variations in water content. For this study, data is collected from 8 (eight) locations in Cikarang Area. Each location consists of dedicated SPT and CPT pairs tests at 2 (two) m distance between each other. After analyzed with various statistical regression analysis of data relevant to this type of soil, a simple linear empirical CPT-SPT correlation with a fairly high correlation has been established allowing test findings to be translated and predicted for the relevant soils type. The simple CPT and SPT correlation is in form of n = qc/NSPT = 0.225 (Mpa), with data distribution of n ranges from 0.15 (Mpa) to 0.33 (Mpa). This results shows much lower n values compared to various correlation have been published worldwide. With respect to the clay soil formation, the low of n-value also reflect a lower density and cohesion bonding clay properties.